(untitled) (Revista Direito em Debate, 2022)
Criminal Liability of a Corporation is a fervently debatable topic and has provoked favorable and unfavorable positions. This is a widely discussed topic in academic circles but the freshness of the topic is maintained even after years. Scholars who are unfavorable to Criminal liability rely on the guilty mind (individual culpability). They say that the legal system do not permit Criminal liability of a Corporation. On the other hand, there are scholars who are in favor of Criminal liability of Corporations and they argue that there must be a new conformation to the theory of crime that only contemplates guilty mind. There is also scholars who defends a collective guilty to explain Criminal liability of Corporation. We argue that the legal system imposes an objective criminal liability as a way of fighting crimes commited by Corporations with great economic power, with support of article 225, §3 of the Federal Constitution of 1988, which was regulated by Law no. 9.605/98 and Brazilian Penal Code.